2023
DOI: 10.3389/fcvm.2022.1037741
|View full text |Cite
|
Sign up to set email alerts
|

Latest advances in biomimetic nanomaterials for diagnosis and treatment of cardiovascular disease

Abstract: Cardiovascular disease remains one of the leading causes of death in China, with increasingly serious negative effects on people and society. Despite significant advances in preventing and treating cardiovascular diseases, such as atrial fibrillation/flutter and heart failure over the last few years, much more remains to be done. Therefore, developing innovative methods for identifying and managing cardiovascular disorders is critical. Nanomaterials provide multiple benefits in biomedicine, primarily better ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 191 publications
0
3
0
Order By: Relevance
“…Comparing cell membrane-camouflaged drug delivery systems to cell-based drug delivery systems, recent research has revealed that the latter can lose all of the native cells’ biological characteristics and functions, including the long lifespan of erythrocytes (red blood cells, or RBCs) in circulation, the ability of macrophages, neutrophils, and mesenchymal stem cells to homing in on inflammation, and the capacity of T cells and natural killer cells to recognize and eliminate tumors [ 192 , 193 , 194 ]. Additionally to the effect of nanocarriers, various physiological and pathological barriers, such as hepatic metabolism, renal filtration, immune clearance, and various organ and tissue barriers (e.g., epithelial–endothelial barrier, extracellular matrix barrier, and cell membrane barrier), control the drug delivery capabilities of mesenchymal stem cells in vivo [ 195 , 196 ].…”
Section: Biotransformation Mechanisms and Clearance Of Mesenchymal St...mentioning
confidence: 99%
“…Comparing cell membrane-camouflaged drug delivery systems to cell-based drug delivery systems, recent research has revealed that the latter can lose all of the native cells’ biological characteristics and functions, including the long lifespan of erythrocytes (red blood cells, or RBCs) in circulation, the ability of macrophages, neutrophils, and mesenchymal stem cells to homing in on inflammation, and the capacity of T cells and natural killer cells to recognize and eliminate tumors [ 192 , 193 , 194 ]. Additionally to the effect of nanocarriers, various physiological and pathological barriers, such as hepatic metabolism, renal filtration, immune clearance, and various organ and tissue barriers (e.g., epithelial–endothelial barrier, extracellular matrix barrier, and cell membrane barrier), control the drug delivery capabilities of mesenchymal stem cells in vivo [ 195 , 196 ].…”
Section: Biotransformation Mechanisms and Clearance Of Mesenchymal St...mentioning
confidence: 99%
“…In recent decades, nanomedicine has drawn attention as a crucial, safe, and effective tool that can be used to treat angiogenic, inflammatory, ischemic, and metabolic diseases like hypertension, atherosclerosis, and hyperlipidemia [4,5,16]. Furthermore, drug delivery, wound healing, stem cell applications, imaging methods, and medical tool design are all presently using nanomedicine [17]. This significant advancement expands on the previously identified uses of NPs, which include their antibacterial, antiviral, and antifungal properties [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These properties make noble metal nanomaterials highly attractive for various biomedical applications. [ 16 ] Specifically, their tunable optical, [ 14 ] electronic, [ 17 ] and catalytic properties [15b,16b] enable the development of innovative strategies for disease diagnosis, [ 18 ] targeted therapy, [ 19 ] and noninvasive imaging. [ 20 ] Tailored structures of nanomaterials play a vital role in advanced biomedical platforms.…”
Section: Introductionmentioning
confidence: 99%